Pertimbangan Hakim dalam Putusan Pembatalan Perkawinan Akibat Paksaan (Studi Putusan Nomor 1332/Pdt.G/2024/PA.Klt) - Ilfi, Zita Melissa; Sukma, Dara Pustika; Hastuti , Luthfiyah Trini (Indonesian Journal of Social Sciences and Humanities, 2026)
This study analyzes aims to determine the legal basis and considerations of the judge in the case of annulment of marriage based on Decision Number 1332/Pdt.G/2024/PA.Klt as well as the regulations regarding the proof of the element of coercion which is the basis for annulment of marriage. This article is a normative legal research conducted by reviewing various legal regulations in the form of laws, regulations, and literature containing theoretical concepts then connected to the problems to be discussed. The approach of this article uses a case study approach (case approach) and a conceptual approach (conceptual approach) based on the Klaten Court Decision Number 1332/Pdt.G/2024/PA.Klt which has permanent legal force. Based on the research results, it was found that the Judge's consideration in the decision to annul a marriage due to coercion refers to Article 6 paragraph (1) of Law Number 1 of 1974 concerning Marriage as amended by Law Number 16 of 2019 and Article 71 letter f of the Compilation of Islamic Law where a marriage can be annulled if the marriage is carried out with an element of coercion and without the consent of both prospective bride and groom. In addition, the Panel of Judges assessed that the Plaintiff's witness statement did not meet the material requirements of evidence because it was only in the form of testimonium de auditu in accordance with Article 171 HIR and Article 1907 of the Civil Code so that it did not have the power of proof, the judge ex officio ordered the Plaintiff to take a suppletoir oath which was deemed to meet the formal and material requirements and was related to the main point of the main point of the case.